2011
DOI: 10.1007/s11357-011-9211-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequential stages in the age-dependent gradual formation and accumulation of tubular aggregates in fast twitch muscle fibers: SERCA and calsequestrin involvement

Abstract: Tubular aggregates (TAs), ordered arrays of elongated sarcoplasmic reticulum (SR) tubules, are present in skeletal muscle from patients with myopathies and are also experimentally induced by extreme anoxia. In wild-type mice TAs develop in a clear age-, sex-(male), and fiber type-(fast twitch) dependence. However, the events preceding the appearance of TAs have not been explored. We investigated the sequential stages leading to the initial appearance and maturation of TAs in EDL from male mice. TAs' formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 40 publications
4
73
0
Order By: Relevance
“…Furthermore, a previous study has shown that Casq and Serca both participate in TA development. As TAs appear to be associated with myopathy, Serca located in the TA membrane has been suggested to be inactivated or functionally compromised (Boncompagni, Protasi & Franzini‐Armstrong, 2012). Consistent with the above, our current findings in mice, and previous findings using a rat model (Sharov, Dremina, Galeva, Williams & Schoneich, 2006), have both revealed that Serca activity decreases in an age‐dependent manner and this decrease in Serca activity is correlated inversely with increased oxidative modification, namely cysteine sulfonation and 3‐nitrotyrosine, which occurs as a consequence of oxidative stress and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study has shown that Casq and Serca both participate in TA development. As TAs appear to be associated with myopathy, Serca located in the TA membrane has been suggested to be inactivated or functionally compromised (Boncompagni, Protasi & Franzini‐Armstrong, 2012). Consistent with the above, our current findings in mice, and previous findings using a rat model (Sharov, Dremina, Galeva, Williams & Schoneich, 2006), have both revealed that Serca activity decreases in an age‐dependent manner and this decrease in Serca activity is correlated inversely with increased oxidative modification, namely cysteine sulfonation and 3‐nitrotyrosine, which occurs as a consequence of oxidative stress and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopic examination revealed that these inclusions consisted of dilated and accumulated sarcoplasmic reticula arranging in an orderly manner. In wild-type mice, they are known as tubular aggregates in muscle cells and reported to be detected only in male mice (Agbulut et al, 2000;Boncompagni et al, 2012). Therefore, it was interesting that in NOG mice, the change occurred not only in males but also in females.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular aggregates originate from the SR,18 23 24 and it has been proposed that sequential formation of aggregates in ageing skeletal muscle fibres is initiated by swelling of the SR cisternae and their extension into longitudinally oriented tubules 22. Different proteins involved in the uptake and the storage of Ca 2+ such as STIM1, SERCA1, RYR1, sarcalumenin or triadin were previously shown to be components of the aggregates 16 18.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular aggregates are the only histopathological hallmark in tubular aggregate myopathy and were most often detected in type II muscle fibres. They also appear in muscle disorders as hypokalemic periodic paralysis19 or congenital limb-girdle myasthenia,20 21 and strikingly accumulate in normal muscle with age in mammals 22…”
Section: Introductionmentioning
confidence: 99%